EVALUASI GEOMETRI PELEDAKAN UNTUK MENGOPTIMALKAN FRAGMENTASI PADA PENAMBANGAN BATU GAMPING DI PT. SEMEN PADANG, PROVINSI SUMATERA BARAT - Febylina Valencia Agustina Rumwaropen; Heriyadi Bambang (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. In an industrial mineral mine, rocks are often found which are relatively hard and cannot be mined freely, so it is necessary to carry out a blasting process. The rock crushing process is carried out to reduce the size of the rock, making it easier to transport into the conveyance. Rock scavenging activities can be carried out in various ways, the method used depends on the nature and characteristics of the rock itself. The effectiveness of blasting activities is one of the benchmarks for the success of loading material which greatly affects the achievement of mining productivity targets. Blasting geometry is one thing that can be controlled. This study aims to evaluate the geometry of blasting by predicting the fragmentation of blasting results at PT. Semen Padang. Prediction of fragmentation in this study using the Kuz-Ram model and Split desktop 2.0 software. To validate the method used, the correlation coefficient (R²) and Root Mean Square Error (RMSE) will be analyzed between the actual measurement using split desktop software and the prediction method used. This study evaluates the geometry of blasting using the theory of R.L. Ash and C.J. Konya. Based on the data analysis conducted, the average percentage of escape is more than 80 cm from the calculation of fragmentation of the actual blasting results, namely 69.744% with a boulder percentage of 30.227%. Meanwhile, based on the data analysis performed, the average percentage that passes is more than 80 cm from the calculation of fragmentation of the Kuz-Ram model is 73% and the percentage retained by the Kuz-Ram model is 27%. To reduce the number of boulder percentages, it is necessary to evaluate the geometry of the blasting based on the R.LAsh and C.J.Konya theories which get the proposed geometry, namely the R.LAsh theory with a burden of 2.6 m, spacing of 3 m, hole depth of 8 m, height of ladder 7 m, column filling 3 ,4 m, stemming 2.6 m, subdrilling 1.04 m and powder factor 0.3 using the Kuz-Ram model, the percentage of boulder is 4.3%, thus the number of boulder becomes less.Keywords: Blasting Fragmentation, R.L.Ash Theory, C.J.Konya Theory, Kuz-Ram Model